Parent-reported offering of allergen foods to infants during complementary feeding : an observational study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics at Massey University, Albany, New Zealand - Medemblik, Jade (Massey University, 2023)
Background: The prevalence of food allergies in New Zealand infants is unknown; however, it is thought to be similar to Australia, where the prevalence is over 10% of infants 12 months of age. Current New Zealand recommendations for reducing the risk of food allergies are to: offer all infants major food allergens (age-appropriate texture) at the start of complementary feeding (around six months), ensure major allergens are given to all infants before 12 months; maintain tolerance of major food allergens by regularly (approximately twice a week) offering the food; and to continue breastfeeding while introducing complementary foods. We know little about parental practices around introducing major food allergens during complementary feeding. Aim: The study aims to explore parental offering of major food allergens to infants during complementary feeding and parent-reported food allergies. Methods: The cross-sectional study included 625 parent-infant dyads from the multi-centred (Auckland and Dunedin) First Foods New Zealand study. Participants were recruited in 2020-2022, and infants were 7-10 months of age. This secondary analysis included the use of study questionnaire and 24-hour diet recall data. The questionnaire included determining current breastfeeding status, offering of major food allergens, avoidance of foods during the infant's first year of life, infant food allergies and their diagnosis. For assessing consumers of major food allergens, 24-hour diet recall data were used (two days per infant). Results: The questionnaire was used to determine that all major food allergens were offered to 9.1% of infants aged 7-10 months and 17% of infants aged 9-10 months. Dairy (94.4%) and wheat (91.2%) were the most common major food allergens consumed on the diet recall days. Breastfed infants (n=414) were more likely to consume sesame than non-breastfed infants (n=211) (48.8% vs 33.7%, p≤0.001). Overall, 12.6% of infants had a parent-reported food allergy and a symptomatic response after exposure was the most common diagnostic tool. Conclusion: Most infants are not offered all major food allergens during early complementary feeding. Only 17% of infants aged 9-10 months were offered all major food allergens, with some parents actively avoiding major food allergens in the first year of life.
Keywords: 321004 Nutritional science